DIFFERENTIAL COSTS. - Rorem, C. Rufus (The Accounting Review, 1928)
Abstract The determining factor in the establishment of any given business policy is a comparison of the additional income and the additional cost expected to result therefrom. If the former exceeds the latter, the action based on the policy is profitable to an enterprise, regardless of the costs which have been incurred previous to any single business decision. The foregoing principle applies to any given business decision, ranging from a produce dealer's problem of accepting an additional order for 100 pounds of butter at a given price, to a capitalist's problem of whether to build and operate an automobile factory. Differential costs may be defined as the costs which must be incurred if an additional unit of business activity is undertaken, and which seed would be incurred if this additional unit of business activity is not undertaken. All other costs may be designated as residual costs, from the standpoint of that particular portion of output or group of operation, the differential cost of which is being calculated.